Sustaining the other or return life: «Masa» by César Vallejo - Rivera, Fernando (2023)
The poem «Masa» by César Vallejo presents a scene where the love of all humans has the power to bring a human being back to life. Love is addressed to the corpse insofar as the body is a place of existence and makes it rise as a human being. The poem confronts death, which implies a radical reification or objectification, through this love whose logic is dependent on Andean rationality. Considering the poem as a poetic reflection on the constitution of human existence, this article analyses Vallejo’s inscription of the life-death relationship as subjectificationobjectification. This allows us to understand the construction of subjectivity as the work of others that sustains the subject through the offer of love. Also, it allows us to approach from a different perspective to contemporary debates that discuss the constitution of human beings as subjects or objects. It implies to reinscribe or dismiss them; for example, the debates of euthanasia or pro-life vs pro-choice.